PENGARUH TRUST, STORE IMAGE, DAN CUSTOMER SATISFACTION TERHADAP CUSTOMER LOYALTY PADA MINIMARKET SEVEN CEMARA JALAN KALIURANG KM.5 YOGYAKARTA - Angga Dwi Hermawan (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine the effect of Trust, Store Image, and Customer Satisfaction in Customer Loyalty at the Seven Cemara store in Yogyakarta. Variables used in this research are Dependent Variable (Customer Loyalty) and the Independent Variable (Trust, Store Image, and Customer Satisfaction).The approach that used in this research is correlational approaching.The population in this study werecustomers which is Seven Cemara store in Yogyakarta. Total of 100persons which accidental sampling.This study uses data source premiere. The primary data collection in this research are doing by distributing questionnaires. The results showed that the influence of Trust, Store Image, and Customer Satisfaction simultaneously to Customer Loyalty indicated by the value of Adjusted R Square of 0.848. That is, 84.8% of Customer Loyalty influenced by the Trust, Store Image, and Customer Satisfaction.